2014
DOI: 10.3892/mco.2014.283
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical gastrectomy versus traditional open surgery in elderly patients with gastric cancer: Benefits and complications

Abstract: Abstract. This study was conducted to compare the therapeutic effect and complications of laparoscopic radical gastrectomy (LRG) Compared to traditional open surgery, LRG exhibited several advantages, such as being less invasive, with less intraoperative blood loss, shorter bedbound time, less intubation time, low frequency of fever, less time to normal diet, shorter hospital stay and a low overall incidence of complications. No significant difference was observed between laparoscopic and open surgery in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…No significant differences were observed in the incidence of postoperative complications, which occurred in eight patients (11.4 %) in the elderly cohort and 10 (8.1 %) in the non-elderly cohort (P = 0.449). Previous studies of postoperative complications in elderly patients after laparoscopic gastrectomy for gastric cancer reported incidences rates ranging from 11.5 to 16.8 % [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were observed in the incidence of postoperative complications, which occurred in eight patients (11.4 %) in the elderly cohort and 10 (8.1 %) in the non-elderly cohort (P = 0.449). Previous studies of postoperative complications in elderly patients after laparoscopic gastrectomy for gastric cancer reported incidences rates ranging from 11.5 to 16.8 % [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that accelerated postoperative rehabilitation reduced health care costs for patients with gastric cancer (Li et al 2014). In the present study, the total hospital costs for gastric cancer patients in the experimental group were significantly lower than those for patients in the control group.…”
Section: Immune Function and Nutritional Statuscontrasting
confidence: 45%
“…Patients with gastric cancer often experience postsurgical eating difficulties because of increased catabolism, weakened anabolism, and decreased immune function. These effects can lead to (or aggravate) malnutrition and increase the incidence of postoperative complications and mortality (Li et al, 2014). Proper nutritional support can significantly improve patients' postsurgical quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%